Analisis Sistem Penghapusan Aset / Barang Milik Daerah pada Badan Pengelolaanokeuangan Dan Aset Daerah (BPKAD) Provinsi Sumatera Utara - Kinanti Putri Bestari; Azhari Akmal Tarigan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Assets are all goods purchased oor obtained at the expense of the State Revenue and ExpenditureoBudget or derived from other legitimateoacquisitions. The abolition of state property isothe finaloactivity of the management of state propertyoand is not a simple act for governmentoagencies. Publication of decisions onothe Elimination oof stateoproperty ooccurs throughoprocedures that are oftenoconsideredocomplicated and a wasteoof time. This study aims toodetermine whetherothe system andoprocedures for the elimination of StateoProperty at the State Property Office at theoRegional Financial and AssetoManagement Agency (BPKAD)oOffice of North Sumatra Province are in accordance with Minister of Finance Regulation 83/PMK.06/2016 concerning Procedures for Implementation Destruction and Eliminationoof State Property. The research method used in this study is a qualitative descriptiveomethod, with the aim of whichoeachodata is collected, analyzed, then a conclusion isodrawn and the type of research used is descriptive qualitative. The results of this study conclude thatothe systemoand procedures forothe elimination of state property at the State Property Office at theoRegional Office of the Ministry ofoReligion of NorthoSulawesi Province are in accordance with the Regulation of theoMinister of Finance Number 83/PMK.06/2016 concerning Procedures for theoExtermination and Elimination of State Property. Keywords: Analysis, Systems and Procedures, Elimination of State Property